Boron nitride particles, resin composition, and method for producing resin composition
By using bent-shaped boron nitride particles, the problem of insufficient contact between boron nitride particles in the prior art is solved and more efficient thermal conductivity is achieved.
Patent Information
- Application Number
- CN202180038612.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-20
- Filing Date
- 2021-08-19
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-08-19
AI Technical Summary
The spherical shape of the existing boron nitride particles causes insufficient contact with each other in the heat dissipation material, affecting the thermal conductivity.
Bent-shaped boron nitride particles are used, which are extended in the first direction and the second direction through a specific generation process, and have a shell portion and a hollow portion formed of boron nitride to increase the contact area between the particles. .
By forming thermal pathways three-dimensionally, the thermal conductivity and overall performance of the heat dissipation material is significantly improved.
Smart Images

Figure CN115768720B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to boron nitride particles, a resin composition, and a method for producing the resin composition. Background Art
[0002] Boron nitride has lubricity, high thermal conductivity and insulation, and is used in various applications such as solid lubricants, mold release materials, raw materials for cosmetics, heat dissipation materials, and sintered bodies with heat resistance and insulation. In the past, boron nitride particles (boron nitride aggregate particles) were usually aggregated particles with a shape close to a sphere, formed by aggregating a plurality of boron nitride primary particles, in order to suppress the anisotropy of the thermal conductivity caused by the crystal structure and scaly shape of hexagonal boron nitride particles.
[0003] For example, Patent Document 1 discloses a hexagonal boron nitride powder that can impart high thermal conductivity and high insulation resistance to a resin composition filled with a resin, wherein the hexagonal boron nitride powder comprises aggregated particles formed of primary particles of hexagonal boron nitride and has a BET specific surface area of 0.7 to 1.3 m 2 / g, and the oil absorption measured based on JIS K 5101-13-1 is 80 g / 100 g or less.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-160134 Summary of the invention
[0007] Problems to be solved by the invention
[0008] When boron nitride particles having a shape close to a sphere are used in, for example, a heat sink, the contact between the boron nitride particles in the heat sink is not necessarily sufficient due to the shape, and there is room for further improvement.
[0009] The main purpose of the present invention is to provide novel boron nitride particles.
[0010] Means for solving problems
[0011] One aspect of the present invention is a boron nitride particle having a bent shape.
[0012] When a straight line L1 connecting a point on one end of the boron nitride particle and a point on the other end and a perpendicular line L2 connecting the straight line L1 or an extension of the straight line L1 to a point on the boron nitride particle are drawn and the length of the perpendicular line L2 becomes the largest, the ratio of the length of the perpendicular line L2 to the length of the straight line L1 can be greater than 0.2.
[0013] The boron nitride particles may include: a first portion extending in a first direction with a length of 50 μm or more; and a second portion bent from the first portion and extending in a second direction different from the first direction with a length of 50 μm or more.
[0014] The boron nitride particles may include an outer shell portion formed of boron nitride and a hollow portion surrounded by the outer shell portion.
[0015] Another aspect of the present invention is a resin composition comprising the above-mentioned boron nitride particles and a resin.
[0016] Another aspect of the present invention is a method for producing a resin composition, comprising the steps of: preparing the boron nitride particles; and mixing the boron nitride particles with a resin. The method for producing a resin composition may further comprise a step of pulverizing the boron nitride particles.
[0017] Effects of the Invention
[0018] According to one aspect of the present invention, novel boron nitride particles can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] [ Figure 1 ] is a schematic diagram showing one embodiment of boron nitride particles.
[0020] [ Figure 2 ] is a graph showing the X-ray diffraction measurement results of the boron nitride particles of Example 1.
[0021] [ Figure 3 ] is a SEM image of the boron nitride particles of Example 1.
[0022] [ Figure 4 ] is a SEM image of the boron nitride particles of Example 2.
[0023] [ Figure 5 ] is a SEM image of the boron nitride particles of Example 3. DETAILED DESCRIPTION
[0024] Hereinafter, embodiments of the present invention will be described in detail. One embodiment of the present invention is a boron nitride particle having a bent shape.
[0025] In the past, boron nitride particles were, for example, spherical in shape, whereas the boron nitride particles according to one embodiment have a bent shape. The boron nitride particles have a bent shape, so that they are easily in contact with other boron nitride particles. Therefore, it is believed that, for example, when the boron nitride particles are mixed with a resin as a heat dissipation material (heat sink), the heat dissipation material has excellent thermal conductivity due to the three-dimensional formation of a heat conduction path formed by the boron nitride particles. Therefore, the boron nitride particles can be preferably used for heat dissipation materials. It should be noted that, although the use of heat dissipation materials as boron nitride particles is illustrated, the boron nitride particles are not limited to heat dissipation materials and can be used for various purposes.
[0026] Figure 1 FIG. 1 is a schematic diagram showing one embodiment of boron nitride particles. Figure 1 As shown in FIG. 1 , in one embodiment, the boron nitride particle 1 includes, for example, a first portion 1a extending in a first direction, and a second portion 1b bent from the first portion 1a and extending in a second direction different from the first direction. The fact that the boron nitride particle has such a bent shape can be confirmed by observing the boron nitride particle with a scanning electron microscope (SEM). Specifically, Figure 1 As shown, in the SEM image of the boron nitride particle 1, when a straight line L1 is drawn connecting an arbitrary point P1 on one end (the end of the first part 1a) 1c of the boron nitride particle 1 and an arbitrary point P2 on the other end (the end of the second part 1b) 1d, if a straight line L1 can be drawn passing through a region R where no boron nitride particle 1 exists, it is judged that the boron nitride particle 1 has a bent shape.
[0027] The bending condition of the boron nitride particles can be evaluated, for example, by the bending index defined as follows. Figure 1 As shown, first, in the SEM image of the boron nitride particle 1, a point P3 is determined where the length of a perpendicular line drawn from the straight line L1 or its extension to a point on the boron nitride particle 1 becomes the maximum, and a perpendicular line L2 is drawn from the point P3 relative to the straight line L1 or its extension. At this time, the bending index is defined as the ratio of the length of the perpendicular line L2 to the length of the straight line L1 (bending index = length of the perpendicular line L2 / length of the straight line L1). The length of the straight line L1 and the length of the perpendicular line L2 can also be measured by importing the SEM image into image analysis software (for example, "Mac-view" manufactured by MOUNTECH Co., Ltd.).
[0028] The greater the bending index, the greater the boron nitride particle bends (at a more acute angle). The bending index of the boron nitride particle can be greater than 0.2, greater than 0.3, greater than 0.4, greater than 0.5, greater than 0.6, greater than 0.7, greater than 0.8, greater than 0.9, greater than 1.0, greater than 1.5, greater than 2.0, or greater than 3.0, and can be less than 10, less than 8.0, less than 6.0, less than 5.0, or less than 4.0. It should be noted that multiple straight lines L1 can be drawn for a boron nitride particle, but as long as at least one straight line L1 with a bending index of the boron nitride particle in the above range can be drawn, the bending index of the boron nitride particle is set to the above range. Below, the numerical range involved for the straight line L1 is the same.
[0029] The length of the straight line L1 may be 50 μm or more, 60 μm or more, 70 μm or more, 80 μm or more, 90 μm or more, 100 μm or more, 150 μm or more, 200 μm or more, or 250 μm or more, and may be 500 μm or less, or 400 μm or less. The length of the vertical line L2 may be 30 μm or more, 40 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, 80 μm or more, 90 μm or more, 100 μm or more, 150 μm or more, 200 μm or more, or 250 μm or more, and may be 500 μm or less, or 400 μm or less.
[0030] The angle formed by the first portion 1a (first direction) and the second portion 1b (second direction) may be 20 to 150°. The angle may be greater than 30°, greater than 40°, greater than 50°, or greater than 60°, and may be less than 140°, less than 120°, or less than 100°.
[0031] The angle formed by the first portion 1a (first direction) and the second portion 1b (second direction) is defined as follows. Figure 1 As shown, a straight line L3 is used to connect point P3 and point P1 on one end (end of first portion 1a) 1c of boron nitride particle 1, and a straight line L4 is used to connect point P3 and point P2 on the other end (end of second portion 1b) 1d. At this time, the angle formed by straight line L3 and straight line L4 is Defined as the angle formed by the first portion 1a (first direction) and the second portion 1b (second direction).
[0032] The lengths of the first portion 1a and the second portion 1b may be independently 50 μm or more, 60 μm or more, 70 μm or more, 80 μm or more, 90 μm or more, 100 μm or more, 150 μm or more, or 200 μm or more, and may be 500 μm or less, 400 μm or less, or 300 μm or less. It is believed that since the boron nitride particles 1 have relatively large first portions 1a and second portions 1b, when the boron nitride particles 1 are mixed with a resin to form a heat dissipation material, the thickness direction of the heat dissipation material can be easily aligned with the first direction or the second direction of the boron nitride particles 1, thereby improving the thermal conductivity of the heat dissipation material in the thickness direction.
[0033] The length of the first portion 1a is defined as the length of the straight line L3. The length of the second portion is defined as the length of the straight line L4. The lengths of the first portion 1a and the second portion 1b can also be measured by importing the SEM image into image analysis software (e.g., "Mac-view" manufactured by MOUNTECH Co., Ltd.).
[0034] The aspect ratios of the first portion 1a and the second portion 1b may independently be 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, 1.5 or more, 2.0 or more, or 3.0 or less, and 12.0 or less, 10.0 or less, 9.0 or less, 8.0 or less, 7.0 or less, or 6.0 or less.
[0035] The aspect ratio of the first portion is defined as the ratio (L3 / L5) of the length (L3) of the first portion to the maximum length (L5) in the direction perpendicular to the direction having the length of the first portion. The maximum length (L5) in the direction perpendicular to the direction having the length of the first portion can be measured in the same way as the length (L3) of the first portion. The aspect ratio of the second portion is defined by replacing the "first portion" in the above definition with "second portion".
[0036] Boron nitride particles can be solid or hollow. When the boron nitride particles are hollow, the boron nitride particles can have an outer shell formed by boron nitride and a hollow portion surrounded by the outer shell. The hollow portion can extend along the bent shape of the boron nitride particles, or it can be a shape roughly similar to the bent shape of the boron nitride particles. In this case, at least one of the ends of the boron nitride particles can be an open end, or all ends can be open ends. The open end can be connected to the above-mentioned hollow portion. By making the boron nitride particles hollow and at least one of the ends of the boron nitride particles an open end, for example, when the boron nitride particles are mixed with a resin and used as a heat dissipation material, by filling the hollow portion with a resin that is lighter than the boron nitride particles, it is possible to simultaneously expect to have thermal conductivity and lightweight heat dissipation materials.
[0037] The boron nitride particles may be substantially composed of only boron nitride. That the boron nitride particles are substantially composed of only boron nitride can be confirmed by detecting only a peak derived from boron nitride in X-ray diffraction measurement.
[0038] Then, the method for producing the above-mentioned boron nitride particles is described below. The above-mentioned boron nitride particles can be produced by, for example, a method for producing boron nitride particles having the following steps: a mixture containing boron carbide and boric acid is arranged in a container formed of a carbon material, and a substrate formed of a carbon material is arranged in such a manner that the substrate surface is approximately parallel to the direction of gravity (arrangement step); a step of generating boron nitride particles on the surface of the above-mentioned substrate by heating and pressurizing the container in a nitrogen atmosphere (generation step). Another embodiment of the present invention is a method for producing such boron nitride particles. It is believed that the boron nitride particles are generated in a direction approximately perpendicular to the substrate surface, but the surface of the substrate through which the boron nitride particles are generated is approximately parallel to the direction of gravity, so that the boron nitride particles are bent due to the influence of gravity in the middle of the generation, so that boron nitride particles with a bent shape can be produced.
[0039] The container formed by the carbon material is a container capable of accommodating the above-mentioned mixture and the substrate. The container may be, for example, a carbon crucible. The container is preferably a container that can improve airtightness by covering the opening with a lid. In the configuration process, for example, the mixture may be configured at the bottom of the container, and the substrate may be configured in the container in such a way that the surface on which the boron nitride particles are generated is in the same direction as the direction of gravity. As for the configuration location of the substrate, if it is in the container, it may be near the center or on the side wall. The closer the configuration location of the substrate is to the center of the container, the easier it is to generate boron nitride particles with a clearly bent shape. The substrate formed by the carbon material may be, for example, in the form of a sheet, a plate or a rod. The substrate formed by the carbon material may be, for example, a carbon sheet (graphite sheet), a carbon plate or a carbon rod.
[0040] The boron carbide in the mixture may be in a powdered state (boron carbide powder), for example. The boric acid in the mixture may be in a powdered state (boric acid powder), for example. The mixture may be obtained by mixing boron carbide powder, boron nitride powder and boric acid powder by a known method.
[0041] Boron carbide powder can be manufactured by a known manufacturing method. As a manufacturing method of boron carbide powder, for example, the following method can be cited: after mixing boric acid and acetylene black, heating at 1800 to 2400° C. for 1 to 10 hours in an inert gas (e.g., nitrogen gas) atmosphere to obtain blocky boron carbide particles. The blocky boron carbide particles obtained by this method are appropriately crushed, sieved, cleaned, impurity removed, dried, etc. to obtain boron carbide powder.
[0042] By adjusting the pulverization time of the massive carbon-boron particles, the average particle size of the boron carbide powder can be adjusted. The average particle size of the boron carbide powder can be 5 μm or more, 7 μm or more, or 10 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, or 70 μm or less. The average particle size of the boron carbide powder can be measured by laser diffraction scattering method.
[0043] The mixing ratio of boron carbide and boric acid can be appropriately selected. From the viewpoint that the boron nitride particles are easily enlarged, relative to 100 parts by mass of boron carbide, the content of boric acid in the mixture is preferably 2 parts by mass or more, more preferably 5 parts by mass or more, further preferably 8 parts by mass or more, and can be 100 parts by mass or less, 90 parts by mass or less, or 80 parts by mass or less.
[0044] As the content of boric acid in the mixture increases, the generated boron nitride particles tend to become larger, so that in the process of generating the boron nitride particles, adjacent boron nitride particles may be bonded to each other, thereby generating boron nitride particles having a bent shape.
[0045] The mixture containing boron carbide and boric acid may also contain other components. As other components, silicon carbide, carbon, iron oxide, etc. can be cited. By the mixture containing boron carbide and boric acid also containing silicon carbide, it is easy to obtain boron nitride particles without open ends.
[0046] The container is provided with a nitrogen atmosphere containing, for example, 95% by volume or more of nitrogen gas. The content of nitrogen gas in the nitrogen atmosphere is preferably 95% by volume or more, more preferably 99.9% by volume or more, and can be substantially 100% by volume. In addition to nitrogen gas, the nitrogen atmosphere may also contain ammonia gas or the like.
[0047] From the viewpoint that the boron nitride particles tend to grow larger, the heating temperature is preferably 1450° C. or higher, more preferably 1600° C. or higher, and further preferably 1800° C. or higher. The heating temperature may be 2400° C. or lower, 2300° C. or lower, or 2200° C. or lower.
[0048] From the viewpoint that the boron nitride particles are likely to grow larger, the pressure during pressurization is preferably 0.3 MPa or more, and more preferably 0.6 MPa or more. The pressure during pressurization may be 1.0 MPa or less, or 0.9 MPa or less.
[0049] From the viewpoint that the boron nitride particles are likely to grow larger, the heating and pressurizing time is preferably 3 hours or longer, more preferably 5 hours or longer. The heating and pressurizing time may be 40 hours or shorter, or 30 hours or shorter.
[0050] According to the manufacturing method, the above-mentioned boron nitride particles can be generated on a substrate formed of a carbon material. Therefore, by recovering the boron nitride particles on the substrate, boron nitride particles can be obtained. In the case where the particles generated on the substrate are boron nitride particles, it can be confirmed by recovering a part of the particles from the substrate, performing X-ray diffraction measurement on the recovered particles, and detecting peaks from boron nitride.
[0051] The boron nitride particles obtained by the above method may be subjected to a step of classifying so as to obtain only boron nitride particles having a maximum length within a specific range (classification step).
[0052] The boron nitride particles obtained by the above method can be mixed with a resin to be used as a resin composition. That is, another embodiment of the present invention is a resin composition containing the above-mentioned boron nitride particles and a resin.
[0053] Examples of the resin include epoxy resins, silicone resins, silicone rubbers, acrylic resins, phenolic resins, melamine resins, urea resins, unsaturated polyesters, fluororesins, polyimides, polyamide-imides, polyetherimides, polybutylene terephthalate, polyethylene terephthalate, polyphenylene ether, polyphenylene sulfide, wholly aromatic polyesters, polysulfones, liquid crystal polymers, polyethersulfones, polycarbonates, maleimide-modified resins, ABS (acrylonitrile-butadiene-styrene) resins, AAS (acrylonitrile-acrylic rubber·styrene) resins, AES (acrylonitrile·ethylene·propylene·diene rubber-styrene) resins, and the like.
[0054] When the resin composition is used as a heat dissipation material, from the viewpoint of improving the thermal conductivity of the heat dissipation material and facilitating obtaining excellent heat dissipation performance, the content of the boron nitride particles may be 15% by volume or more, 20% by volume or more, 30% by volume or more, 40% by volume or more, 50% by volume or more, or 60% by volume or more based on the total volume of the resin composition. From the viewpoint of being able to suppress the generation of voids when the resin composition is molded into a sheet-like heat dissipation material and suppressing the decrease in the insulation and mechanical strength of the sheet-like heat dissipation material, the content of the boron nitride particles may be 85% by volume or less, 80% by volume or less, 70% by volume or less, 60% by volume or less, 50% by volume or less, or 40% by volume or less based on the total volume of the resin composition.
[0055] The content of the resin can be appropriately adjusted according to the application of the resin composition, required characteristics, etc. Based on the total volume of the resin composition, the content of the resin can be, for example, 15% by volume or more, 20% by volume or more, 30% by volume or more, 40% by volume or more, 50% by volume or more, or 60% by volume or more, and can be 85% by volume or less, 70% by volume or less, 60% by volume or less, 50% by volume or less, or 40% by volume or less.
[0056] The resin composition may further contain a curing agent for curing the resin. The curing agent may be appropriately selected according to the type of the resin. For example, as a curing agent used together with the epoxy resin, phenolic Novolac compounds, acid anhydrides, amino compounds, imidazole compounds, etc. may be cited. Relative to 100 parts by mass of the resin, the content of the curing agent may be, for example, 0.5 parts by mass or more, or 1.0 parts by mass or more, or 15 parts by mass or less, or 10 parts by mass or less.
[0057] The resin composition may further contain other components, such as a curing accelerator (curing catalyst), a coupling agent, a wetting and dispersing agent, and a surface conditioner.
[0058] Examples of the curing accelerator (curing catalyst) include phosphorus-based curing accelerators such as tetraphenylphosphine tetraphenylborate and triphenylphosphate, imidazole-based curing accelerators such as 2-phenyl-4,5-dihydroxymethylimidazole, and amine-based curing accelerators such as boron trifluoride monoethylamine.
[0059] Examples of the coupling agent include silane coupling agents, titanate coupling agents, and aluminate coupling agents, etc. Examples of the chemical bonding groups contained in these coupling agents include vinyl groups, epoxy groups, amino groups, methacryloyl groups, and mercapto groups.
[0060] Examples of the wetting and dispersing agent include phosphate ester salts, carboxylic acid esters, polyesters, acrylic acid copolymers, and block copolymers.
[0061] Examples of the surface conditioner include acrylic surface conditioners, silicone surface conditioners, vinyl surface conditioners, and fluorine surface conditioners.
[0062] The resin composition can be produced, for example, by a method for producing a resin composition comprising the steps of: preparing the boron nitride particles according to one embodiment (preparation step); and mixing the boron nitride particles with a resin (mixing step). Another embodiment of the present invention is a method for producing such a resin composition.
[0063] The method for producing a resin composition according to one embodiment may further include a step of crushing the boron nitride particles (crushing step). The crushing step may be performed between the preparation step and the mixing step, or may be performed simultaneously with the mixing step (the boron nitride particles may also be crushed while mixing the boron nitride particles with the resin).
[0064] The resin composition can be used as a heat dissipation material, for example. The heat dissipation material can be manufactured, for example, by curing the resin composition. The method for curing the resin composition can be appropriately selected according to the type of resin (and curing agent used as needed) contained in the resin composition. For example, when the resin is an epoxy resin and the curing agent is used in combination, the resin can be cured by heating.
[0065] Example
[0066] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples.
[0067] (Example 1)
[0068] The blocky boron carbide particles were crushed by a pulverizer to obtain boron carbide powder with an average particle size of 10 μm. 100 parts by mass of the obtained boron carbide powder was mixed with 9 parts by mass of boric acid, and the obtained mixture was filled in a carbon crucible, and a carbon substrate (manufactured by Tokai Carbon Co., Ltd.) was arranged in the center of the container of the carbon crucible so that the surface of the substrate was roughly parallel to the direction of gravity. The carbon crucible with a lid was heated in a resistance heating furnace at 2000°C and 0.85MPa for 20 hours under the conditions of nitrogen gas atmosphere, thereby generating particles on the above-mentioned surface of the carbon substrate.
[0069] A portion of the particles generated on the surface of the carbon substrate was recovered and subjected to X-ray diffraction measurement using an X-ray diffractometer (manufactured by Rigaku Corporation, "ULTIMA-IV"). The X-ray diffraction measurement results and the X-ray diffraction measurement results of boron nitride powder (GP grade) manufactured by Denka Co., Ltd. as a comparison object are shown in Figure 2 Shown in. Figure 2 It can be seen that only the peak derived from boron nitride was detected, confirming that boron nitride particles were generated. The SEM image of the obtained boron nitride particles is shown in FIG. Figure 3 For one of the obtained boron nitride particles ( Figure 3 The boron nitride particles indicated by arrows in the figure are obtained. Figure 1 The straight lines (perpendicular lines) L1 to L4 and the angles shown The length of the straight line L1 is 72 μm, the length of the perpendicular line L2 is 63 μm, the length of the straight line L3 is 73 μm, the length of the straight line L4 is 72 μm, and the angle The bending angle is 60° and the bending index is 0.88.
[0070] (Example 2)
[0071] The carbon sheet (manufactured by NeoGraf) was placed on the side wall surface of the container of the carbon crucible so that the surface of the carbon sheet was approximately parallel to the gravity direction. Particles were generated on the surface of the carbon sheet in the same manner as in Example 1. A portion of the particles generated on the surface of the carbon sheet was recovered and subjected to X-ray diffraction measurement. As a result, only peaks derived from boron nitride were detected, thereby confirming that boron nitride particles were generated. The SEM image of the obtained boron nitride particles is shown in FIG. Figure 4 For one of the obtained boron nitride particles ( Figure 4 The boron nitride particles indicated by arrows in the figure are obtained. Figure 1 The straight lines (perpendicular lines) L1 to L4 and the angles shown and bending index (= length of perpendicular line L2 / length of straight line L1), the length of straight line L1 is 348 μm, the length of perpendicular line L2 is 140 μm, the length of straight line L3 is 170 μm, the length of straight line L4 is 288 μm, and the angle The bending angle is 95° and the bending index is 0.40.
[0072] (Example 3)
[0073] Particles were generated on the surface of the carbon sheet in the same manner as in Example 2 except that the amount of boric acid was changed to 72 parts by mass. A portion of the particles generated on the carbon sheet was recovered and subjected to X-ray diffraction measurement. As a result, only a peak derived from boron nitride was detected, confirming that boron nitride particles were generated. The SEM image of the obtained boron nitride particles is shown in FIG. Figure 5 For one of the obtained boron nitride particles ( Figure 5 The boron nitride particles indicated by arrows in the figure are obtained. Figure 1 The straight lines (perpendicular lines) L1 to L4 and the angles shown and bending index (= length of perpendicular line L2 / length of straight line L1), the length of straight line L1 is 109 μm, the length of perpendicular line L2 is 232 μm, the length of straight line L3 is 248 μm, the length of straight line L4 is 233 μm, and the angle The bending angle is 26° and the bending index is 2.12.
Claims
1. Boron nitride particles having a bent shape, The boron nitride particles have an outer shell portion formed of boron nitride and a hollow portion surrounded by the outer shell portion. The boron nitride particles have: a first portion extending in the first direction with a length of 50 μm or more; and a second portion bent from the first portion and extending in a second direction different from the first direction by a length of 50 μm or more; The aspect ratio of the first portion is less than 12.0, The aspect ratio of the second portion is 12.0 or less.
2. The boron nitride particles according to claim 1, wherein When a straight line L1 connecting a point on one end of the boron nitride particle and a point on the other end and a perpendicular line L2 whose length is the largest are drawn, the ratio of the length of the perpendicular line L2 to the length of the straight line L1 is greater than 0.
2.
3. A resin composition comprising: a resin and the boron nitride particles according to claim 1 or 2.
4. A method for producing a resin composition, comprising the following steps: A step of preparing the boron nitride particles according to claim 1 or 2; and A step of mixing the boron nitride particles with a resin. 5 . The method for producing a resin composition according to claim 4 , further comprising the step of pulverizing the boron nitride particles.
Citation Information
Patent Citations
Hexagonal boron nitride powder and method for producing the same
JP2016160134A
Sintered spherical BN particles with concave part, method for producing same, and polymer material
CN104470873A
Hexagonal crystal boron nitride particle
JP2016216271A
Isolation structures for electrical systems
US20170133120A1